Comparing inductive and deductive grammatical instruction in teaching German as a foreign language in Dutch classrooms. (December 2016) - Tammenga-Helmantel, Marjon; Bazhutkina, Iryna; Steringa, Sharon; Hummel, Ingrid; Suhre, Cor
Abstract: Recent review studies show that explicit instruction is the most effective way when presenting grammar in a foreign language teaching setting. However, they do not distinguish between types of explicit instruction. This study explores what type of explicit instruction (i.e. deductive or inductive instruction) is more effective for Dutch students learning German. The participants are secondary school students from two different levels of secondary education, viz. HAVO and VWO. We investigate the learning of a complex grammatical structure, the subjunctive for reported speech (Konjunktiv I). Using a pretest-posttest design, we compare the gain scores for a grammaticality judgment test and a writing test for explicit-deductive and explicit-inductive instruction groups and a control group. One-way ANOVA analyses show that both types of explicit instruction have a positive effect on learning gain. Only the grammaticality judgment test displays statistically significant differences between inductive and deductive instruction, with better results for inductive instruction. According to our data the educational level of the participants did not influence the learning effects.